2007
DOI: 10.1021/ol0710111
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclopropanol-Based Strategy for Subunit Coupling:  Total Synthesis of (+)-Spirolaxine Methyl Ether

Abstract: A strategy for ketone synthesis with cyclopropanols as intermediates and its application to (+)-spirolaxine methyl ether is described. The synthesis also features an application of Fu's alkyl-alkyl Suzuki coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Fu et al applied Ni-catalyzed Negishi coupling for the formal synthesis of a-cembra-2,7,11-triene-4,6-diol 63 and Fluvirucinine A1. 49 Phillips et al employed Pd-catalyzed alkyl-alkyl Suzuki coupling for the total synthesis of (+)-Spirolaxine methyl ether 90 and Pyranicin. 91 With the increasing awareness of the synthetic community of these new coupling methodologies, the cross coupling of non-activated alkyl halides is expected to become a standard tool in organic synthesis, benefiting the production of synthetic building blocks, fine and speciality chemicals, agro-chemicals, biologically and pharmaceutically active molecules, and organic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al applied Ni-catalyzed Negishi coupling for the formal synthesis of a-cembra-2,7,11-triene-4,6-diol 63 and Fluvirucinine A1. 49 Phillips et al employed Pd-catalyzed alkyl-alkyl Suzuki coupling for the total synthesis of (+)-Spirolaxine methyl ether 90 and Pyranicin. 91 With the increasing awareness of the synthetic community of these new coupling methodologies, the cross coupling of non-activated alkyl halides is expected to become a standard tool in organic synthesis, benefiting the production of synthetic building blocks, fine and speciality chemicals, agro-chemicals, biologically and pharmaceutically active molecules, and organic materials.…”
Section: Discussionmentioning
confidence: 99%
“…The assignment of absolute stereochemistry for adducts 3a–3t was made in analogy to phthalide 3l , which was determined by single crystal X-ray diffraction, and phthalide 3t , which was evaluated by comparison of its optical rotation to that of an authentic sample. [16] Underscoring the utility of this method in target oriented synthesis, the preparation of 3t constitutes a formal synthesis of two different phthalide natural products: ent -spirolaxine methyl ether [17] and CJ-12,954 (Figure 2). [18] Both compounds have been shown to exhibit antibiotic activity against the Gram-negative bacteria Helicobacter pylori .…”
mentioning
confidence: 99%
“…In 2007 the group based their total synthesis of the polyketide (+)-spirolaxine methyl ether (17) on a late stage alkylalkyl Suzuki cross-coupling key step. 12 The class of the spirolaxines are produced by the white-rod fungi Sporotrichum and Phanerochaetei and show potential as antibiotics against Helicobacter pylori. Additionally, it was reported that (+)-spirolaxine methyl ether (17) inhibits the growth of multiple cell lines and lowers cholesterol levels.…”
Section: Palladium-catalysed Coupling Reactionsmentioning
confidence: 99%